1995
DOI: 10.1089/jir.1995.15.897
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Interferon-γ Induces Endogenous Synthesis of Interferon-α and -β by Murine Macrophages for Induction of Nitric Oxide Synthase

Abstract: Murine macrophages (M phi) are activated either by interferon-gamma (IFN-gamma) or interferon-alpha/beta (IFN-alpha/beta) in combination with bacterial lipopolysaccharide (LPS) to induce synthesis of tumor necrosis factor alpha (TNF-alpha) and nitric oxide synthase (iNOS) mRNA synthesis for generation of tumor cytotoxic nitric oxide (NO). In the present study, the effect of exogenous IFN-gamma on the induction of endogenous mRNA synthesis and secretion of IFN-alpha/beta by murine M phi was investigated. Neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…To characterize better this process, we investigated the activation of NF-B and Stat1␣ as transcription factors integrating the early pro-inflammatory stimulation involved in the transcriptional activation of genes that participate in the onset of inflammation. 8,[30][31][32][33] As Figure 6 shows, NF-B activation in macrophages from animals challenged in vivo with LPS and IFN-␥ was impaired in Tg-1 when compared with the corresponding controls, at least during the initial 2-h period after stimulation. Analysis of the bands by supershift assays suggested the presence of p65.p50 and p50.p50 complexes in the upper and lower bands, respectively.…”
Section: Figure 5 Tnf-␣ and Il-1␤ Levels In Serum And Peritoneal Washmentioning
confidence: 97%
See 3 more Smart Citations
“…To characterize better this process, we investigated the activation of NF-B and Stat1␣ as transcription factors integrating the early pro-inflammatory stimulation involved in the transcriptional activation of genes that participate in the onset of inflammation. 8,[30][31][32][33] As Figure 6 shows, NF-B activation in macrophages from animals challenged in vivo with LPS and IFN-␥ was impaired in Tg-1 when compared with the corresponding controls, at least during the initial 2-h period after stimulation. Analysis of the bands by supershift assays suggested the presence of p65.p50 and p50.p50 complexes in the upper and lower bands, respectively.…”
Section: Figure 5 Tnf-␣ and Il-1␤ Levels In Serum And Peritoneal Washmentioning
confidence: 97%
“…For example, using these animals, it has been reported that hIFN-␤ favors the development of a pre-diabetic state that was evidenced after administration of low doses of streptozotocin. 25 Tg-1 mice released relatively large amounts of hIFN-␤, but because of the much lower affinity of the human cytokine for the murine type I IFN receptor, it exerts systemic effects outside the pancreas where the cytokine is produced, 8 a condition which constitutes an advantage of this model over a murine IFN-␤-expressing alternative. We detected levels of hIFN-␤ that are in the range of 4-5 ng/ml of serum as deduced by ELISA assays.…”
Section: Figure 7 Ifn-␥ Signaling Is Altered In Mice Expressing Hifn-mentioning
confidence: 99%
See 2 more Smart Citations
“…27 However, it has not been found to be as effective as IL-12 both in terms of its own production in vivo, as well as in terms of anti-tumor and anti-metastatic activity. 28 In the earlier paper, we reported that in vitro transfection of PAGA/pmIFN-␥ into cultured CT-26 tumor cells generates similar expression levels of mIFN-␥ in comparison with mIL-12 induced mIFN-␥.…”
Section: Discussionmentioning
confidence: 99%